2006
DOI: 10.1139/p07-001
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stability of the near-Earth plasma sheet during substorms: 9 February 1995 event

Abstract: It has been previously demonstrated that several minutes prior to an onset of a magnetospheric substorm the near-Earth plasma sheet becomes unstable to resonance-type perturbations. The next logical step, examined here, is an assumption that the velocity shear in the resonance would lead to a development of a Kelvin–Helmholtz (KH) instability. Using a Grad-Shafranov equilibrium constrained by CANOPUS data, we analyze the stability properties of the near-Earth plasma sheet in the presence of a field-line resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Various plasma instabilities have been proposed as playing important roles during the substorm onset process. These include the tearing [Schindler, 1974;Sitnov et al, 1997;Zelenyi et al, 2008], ballooning [Cheng and Lui, 1998;Bhattacharjee et al, 1998;Dobias et al, 2004;Zhu et al, 2003;Saito et al, 2008;Friedrich et al, 2001], lower hybrid drift [Shinohara et al, 1998;Yoon et al, 2002;Mok et al, 2006], Kelvin-Helmholtz [Rostoker and Samson, 1984;Dobias et al, 2006], and the ion Weibel [Yoon and Lui, 1993;Sadovskii and Galeev, 2001] instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Various plasma instabilities have been proposed as playing important roles during the substorm onset process. These include the tearing [Schindler, 1974;Sitnov et al, 1997;Zelenyi et al, 2008], ballooning [Cheng and Lui, 1998;Bhattacharjee et al, 1998;Dobias et al, 2004;Zhu et al, 2003;Saito et al, 2008;Friedrich et al, 2001], lower hybrid drift [Shinohara et al, 1998;Yoon et al, 2002;Mok et al, 2006], Kelvin-Helmholtz [Rostoker and Samson, 1984;Dobias et al, 2006], and the ion Weibel [Yoon and Lui, 1993;Sadovskii and Galeev, 2001] instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that if one seeks a trigger then one will tend to find many different possible sources of a substorm onset; it is not the trigger that is so important as the energetic state of the high-latitude magnetosphere. Dobias et al (2004Dobias et al ( , 2007 demonstrated that during the growth phase there is a significant reconfiguration of the free energy in the near-Earth plasma sheet. Using an assumption of FLR-like perturbations present in the system just prior to the onset, they demonstrated that the plasma sheet becomes explosively unstable at the time of the onset.…”
Section: Discussionmentioning
confidence: 99%